Lived Experiences and Coping Styles of Alaskan Women with Opioid Use Disorders - Golden, Faith May (2017)
Death caused by opioid abuse has increased in recent years, and women in the state of Alaska have been significantly impacted by this opioid crisis. Previous researchers have indicated a possible connection between opioid use and sub-clinical PTSD criteria. The purpose of this grounded theory study was to develop a theory regarding the presence of PTSD diagnostic criteria in this population, to identify patterns in past traumas and other life stressors, and to investigate coping strategies in 43 Alaskan women who sought treatment for opioid use. Archived data in the form of therapy notes were analyzed using grounded theory techniques such as coding information, categorizing the codes, and comparing patterns that were discovered to previous research. Hyperarousal was the most commonly reported criterion of PTSD, becoming the basis of the theory that it plays an important role connecting lived experiences and coping in these women. The most commonly reported experiences included substance use by parents, parental divorce, domestic violence, employment issues, mental health issues, partner substance use, and legal issues. Coping strategies included medicating, seeking support from nonprofessionals, and compliance. Recommendations for applying findings included using trauma-informed care, and implementing therapeutic workplaces, to reinforce abstinence with the ability to work as part of treatment. This data can be used for social change by improving assessment and treatment through addressing what might not have previously been considered trauma in these clients. Thus, providers may provide more effective treatment for opioid use disorders, and implement strategies to help prepare clients for longer term success and reduced prevalence of relapse